Mapping Global Research Trends in Fashion Illustration: A Bibliometric Analysis of Scopus-Indexed - Khoiriyah, Asmaul; Nurmasitah, Sita (Journal of Creativity Student, 2026)
Fashion illustration constitutes a significant component of both fashion scholarship and professional practice; however, the global structure and development of research in this field have not yet been systematically mapped. This study aims to analyze publication growth patterns, thematic structures, and evolving research directions in fashion illustration based on Scopus-indexed journal articles published between 2015 and 2025. Adopting a bibliometric research design, the study employs publication performance analysis and keyword co-occurrence mapping using VOSviewer. The findings reveal a steady increase in publication output over the past decade, indicating a growing academic recognition of fashion illustration as a distinct research domain. The keyword co-occurrence network highlights strong thematic associations with visual studies, historical inquiry, and cultural analysis, while linkages to fashion industry practices, sustainability, design technology, and design education remain comparatively underdeveloped. These results suggest that fashion illustration is still predominantly conceptualized as a medium of visual representation, while also revealing significant potential for its transformation into a more integrative and interdisciplinary field that can meaningfully contribute to design education and contemporary creative industries.